Racial disparities in incidence of human papillomavirus-associated oropharyngeal cancer in an urban population. (October 2016) - Ramer, Ilana; Varier, Indu; Zhang, David; Demicco, Elizabeth G.; Posner, Marshall R.; Misiukiewicz, Krzysztof; Genden, Eric M.; Miles, Brett A.; Teng, Marita S.; Sikora, Andrew G.
Highlights: HPVOPC higher among Caucasians than African Americans in an urban population. Racial disparities in HPVOPC rates persist across different levels of urbanization. No significant difference seen in HPVOPC rates among Caucasians and Hispanics. Abstract: Background: Recent studies suggest that rates of human papillomavirus related oropharyngeal cancer (HPVOPC) in the US are higher in Caucasians than minorities. We hypothesized that this disparity would be less marked in a racially and ethnically diverse population from New York City. Methods: This is a retrospective chart review of 210 patients with biopsied or surgically treated OPC at the Icahn School of Medicine at Mount Sinai (ISMMS) between 1999 and 2013. Polymerase chain reaction (PCR) was used to detect the presence of HPV-DNA in paraffin-embedded tumor blocks. Incidence of HPV-positive cancers was compared between Caucasians and minorities (defined as African Americans, Asians, and Hispanics) using Fisher's exact test. Results: We found a higher incidence of HPV-positive OPC in Caucasians than racial minorities within the ISMMS population (p = 0.002). HPV incidence detected by PCR was 139/165 [84.2%] for Caucasians and 28/45 [62.2%] for minorities. Specifically, there was a higher rate in Caucasians compared to African Americans (p = 0.017), but no significant difference between Caucasians and Hispanics (p = 0.087). Conclusion: We documented a disparity in incidence of HPVOPC amongst racial groups, consistent with previously reported trends from study populations in less urbanized areas. Thus we conclude that the factors underlying racial/ethnic disparities in HPVOPC incidence are likely to be similar across communities with different levels of urbanization and population diversity.